Effects of air exposure stress on crustaceans: Histopathological changes, antioxidant and immunity of the red swamp crayfish Procambarus clarkii. (October 2022) - Zhang, Yan-Mei; Xu, Wen-Bin; Cheng, Yuan-Xin; Chen, Da-Yong; Lin, Chen-Yang; Li, Bang-Ze; Dong, Wei-Ren; Shu, Miao-An
Abstract: Air exposure stress may result in oxidative damage and ultimately disease or death in crustaceans. Using the Procambarus clarkia, one of the main commercial aquaculture species in China, as a study model, the molecular mechanism including histopathological changes, antioxidant capacity and immunity response under the air exposure stress were firstly evaluated. Results showed that the surfaces of gill were wrinkled while the morphologies of the nuclei and mitochondria in the hepatopancreas were altered after 48 h of air exposure stress, and the damage of mitochondria was more serious after additional bacterial infection. Moreover, the activity of antioxidant enzymes increased at first and then decreased along with increasement of air exposure time. The concentration of malondialdehyde (MDA) in hepatopancreas was significantly increased under the air exposure stress, while the bacterial infection further aggravated such oxidative damage. The transcriptome analysis exhibited that the stress- and immunity-related genes in hepatopancreas altered when response to the air exposure stress. This study could help uncover the mechanisms of aerial exposure stress responses in Procambarus clarkii . Highlights: Air exposure caused severe histological alterations to P. clarkii hepatopancreas. Air exposure induced oxidative damage to P. clarkii hepatopancreas. Oxidative damage and histological alterations were more serious after additional bacterial infection. GO terms and KEGG pathways were significantly enriched after air exposure and bacterial infection. DEGs related to antioxidant, immune response, etc. were identified.